ANALISIS PENGARUH HASIL INVESTASI, HASIL UNDERWRITING DAN BEBAN KLAIM TERHADAP LABA PERUSAHAAN (Survei pada Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia Tahun 2016 – 2018) - Sari, Mega Aprillia; Sriwidodo, Untung; Indriastuti, Dorothea Ririn (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this study is to analyze the significant influence of investment returns, underwriting, and claim burden on the profits of insurance companies listed on the Indonesia Stock Exchange in 2016 – 2018. This study uses a population of 11 insurance companies listed on the Indonesia Stock Exchange. The sample in this study amounted to 7 companies with a purposive sampling technique. Data analysis techniques used in this study are the classic assumption test, multiple linear analysis and hypothesis testing. The results showed that partially investment returns and claim expenses had a significant effect on company profits, while underwriting results did not significantly influence company profits. Simultaneously investment returns, underwriting results, and claim expenses have an effect on company profits.